EFFECT OF THE SOIL PROTECTION SHEET AND THE BAG MATERIAL ON THE SOIL MICROORGANISMS AND THE INDIGENOUS ARBUSCULAR MYCORRHIZAL FUNGI IN THE VOLCANIC DEVASTATED SITE IN MT. BATUR, BALI, INDONESIA - Kohno, Nobuyuki; Gouya, Kayo; Sekiyama, Shin-ichi; Suzuki, Motoyuki; Wirawan, I Gede Putu (International Journal of Biosciences and Biotechnology; Vol 2 No 2 (2015), 2016)
In the volcanic devastated site of Mt. Batur located in the north eastern part of Bali, Indonesia,the test construction with the soil protection sheet and the bag material for the prevention of soilerosion and the revegetation had been executed in December, 2012 and the effect has beenverified by now. In this study, the effect of the sheet on the soil microorganisms was investigatedand the effect of the indigenous arbuscular mycorrhizal fungi, which had been put into the bagmaterial with 3 kinds of woody plant seeds, on the vegetation was verified. As a result, after 2years and 8 months from the construction, it was showed that the soil microorganisms under thesheet without the plant increased 2 to 2.4 times more than those in the bare site without the plant.Furthermore, those soil microorganisms under the sheet with the plant increased 8.4 to 8.9 timesmore than those in the bare site without the plant. It is considered that the cutting fragments in thelength of about 5cm of the gramineous plant root existed near the construction site put into thebag material with the woody plant seeds contributed to the colonization of the arbuscularmycorrhizal fungi into the roots of seedlings from the seeds and the survival of the seedlings fromthe seeds as the inocula of the fungi.
Keywords: Revegetation; mycorrhizal fungi; protection sheet